SOCIAL, CULTURAL, AND RELIGIOUS ASPECT IN MOSQUE FUNDRAISER - Achmad Naufal Irsyadi; Fachriana Hanifiyah; Suryadi Suryadi (Universitas Airlangga, 2021)
Abstract: This study described and analyzed the form and types of speech in fundraising activity as well as to identify social, cultural, and religious aspect in it. The observation was carried out in Wirolegi Village, Sumbersari District, Jember Regency. This study used a phenomenological perspective which viewed that fundraising activity was a social reality known by the public. This study used anthropolinguistic approach which viewed that people's linguistics activities (speech) were related to the social and cultural systems of the community. To examine the forms and types of speech, this study used Searle's speech act theory. This study resulted a finding that the utterances of the fundraiser were about expressive and commissive speech acts. Thus, the language activity within fundraising program was an action that was clearly and indirectly contained in his speech. In its social aspect, the speech contained a binding from the speaker to the interlocutor which could contribute to their social and religious aspect.